Aromatic compounds in bitumoids of the Bazhenov Formation in the North of the Khantey hemiantheclise - I. S. Sotnich; E. A. Kostyreva (Georesursy)
The main features of the geochemistry of individual aromatic compounds (phenanthrenes, dibenzothiophenes, monoand triaromatic steroids) in chloroform extracts (bitumoids) from the open (regular form and coarse-crushed (≥0.5 cm) samples) and closed (fine-crushed (0.25 mm) samples) pore space of the Bazhenov Formation have been determined. The differences in the aromatic compounds distribution of organic matter of the Bazhenov Formation in the North of the Khantey hemiantheclise (Surgut region, KhantyMansiysk Autonomous District, Western Siberia) are mainly related to its stage of thermal maturity which decreases in the south-west direction within the studying area. The most sensitive to maturity variations at the same catagenesis gradation are the parameters: CPI, Ts/Tm, 1/Ki ((n-C17 + n-C18)/(Pr + Ph)), MDR (4-MDBT/1- MDBT), DBTI ((2+3-MDBT)/DBT) and TASI (TAS I/(TAS I + TAS II)). Based on some indicators (PI, MPI, PP-1, MDR, DBTI etc.), it is possible to notice the decrease and equalization of its values in bitumoids from closed pores compared with those from open ones. It seems to be associated with the removal of the most transformed, light and migratory-capable part of bitumoids during their extraction from the open pore space of rocks.